PENGARUH GAYA KEPEMIMPINAN DEMOKRASI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. MEGA AUTO FINANCE DI SURABAYA - Nuh kartini, I.A; Surayana Metra, Putu Bagus Jaya (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACTHuman Resources (HR) has an important role as a potential driver of all activities of the company. Every company should be able to maintain, maintain and improve the quality of Human Resources (HR) performance. All actions taken in every activity are initiated and determined by the human being who is a member of the company. Primary data source in this study was obtained from PT Mega Auto Finance in Surabaya in the form of questionnaire results. In this research use full sample where PT Mega Auto Finance in Surabaya become population as well as sample. test coefficient of determination obtained R value of 0.736 this R Square number of 73.6%, indicating that Leadership Style, Motivation, Work Discipline is explained by Employee Performance variables, while the rest of (100% - 73.6%) = 26.04% is explained by other factors not included in this research model. Variable X1 (leadership style) t arithmetic equal to 6,848, thus t arithmetic> t table (6,848> 2,410) which statistically stated significant (influential); Variable X2 (motivation) t arithmetic equal to -1.066, thus t arithmetic> t table (-1.066 <2.410) which; Variable X3 (work discipline) t arithmetic equal to -1.593, thus t arithmetic> t table (-1.593 <2.410) statistically, Variable X3 (work discipline) does not affect variable Y (Employee Performance).Â Keywords: Democratic Leadership Style, Motivation, Work Discipline, Employee Performance.Â